O eksplanacyjnych możliwościach kulturowego ujęcia systemowości prawa - Barankiewicz, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The article discusses the issue of cultural understanding of the law. Generally in this study we describe the condition of society of the period of late modernity. First of all, we assume that, on the one hand, law is a certain system of norms founded traditionally according to the principle of non-contradiction, whereas on the other hand, the constituted law cannot be isolated from other regulators of social life. The law is a complex phenomenon and can be analyzed at many levels. However, using the social and cultural argument, the principle of non-contradiction refers to the whole axiological and normative system of a given culture. The cultural approach applied here points to both the diversity as well as the unity of cultural patterns and rules in social life.
Keywords: systemowość prawa; kulturowe ujęcie prawa; system prawa; system aksjonormatywny